Free-Form Dance as an Alternative Interaction for Adult Grandchildren and Their Grandparents - Shuper Engelhard, Einat (Frontiers in Psychology, 2020)
Shared leisure activities fulfill a central role in strengthening the relationship with adult grandchildren and provide a vehicle for transmission of values. Thus, it is likely that joint activity alongside support and focused guidance in communication between adult grandchildren and grandparents will help strengthen their relationship. Based on theory and research on dance/movement therapy in old age, and on development processes in the family, the aim of the present study is to discover the significance of free-form dance jointly engaged in by adult grandchildren with their grandparents, for each of the generations. Using action research, 16 dance-movement therapists and their grandmothers participated in three dance meetings in their grandmothers’ homes. Based on filmed videos of the sessions, personal diaries, and semi-structured interviews it was found that among the granddaughters, the meeting aroused concerns about their lack of skill to create a meaningful meeting and to protect their grandmothers throughout the meeting. It was also found that regular free-form dance meetings in which the granddaughter mirrored her grandmother’s movements while suggesting expansions to the movements, encouraging eye contact, touch, playfulness, and empowering her ability, while also granting legitimacy to rest, created a change in the grandmother’s state of mind: positive memories and feelings appeared, as did uplifted spirits. For the granddaughters, the meeting altered their perspective on old age and provided a space for processes of parting. The implications of identifying assistive components of joint dancing for creating an intervention model for adult grandchildren’s support of the elderly in the community is extensively discussed.